Analisis Pelaksanaan Program Unit Kesehatan Sekolah (UKS) Dengan Perilaku Hidup Bersih dan Sehat di SDN Joglo 08 Pagi - Wibisana, Elang; Azhar, Samsul; Noviliana, Sindi Agnia (YASIN, 2022)
The implementation of UKS programs with PHBS at SDN Joglo 08 Pagi has been going well, although it still has the problem in implementing the UKS program is that some students who sometimes ignore PHBS and UKS programs. This research aims to knowing the implementation of the UKS program with clean and healthy living habits at SDN Joglo 08 Pagi. This research is a descriptive qualitative research by taking data at SDN Joglo 08 Pagi with the subject and object of research Head School. UKS teachers, students grade three, four, five, and UKS. Data collection methods used observation, interviews, and documentation. Data analysis was collected by collecting data, reducing data, presenting data, and drawing conclusions. The results showed that the implementation of UKS programs has been going well, such as the little doctor program runs, immunizations, socialization and counseling are challenged health, both from the national health center and the department of health, every time the program runs is always accompanied by the school commite, although it still has the problem in implementing the UKS program is that some students who sometimes ignore PHBS and UKS programs.